(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Objective: Analysis of bariatric surgery outcomes, risk factors, and prevention of possible complications. Materials and methods. At the multidisciplinary clinic of the Tashkent Medical Academy 120 patients underwent bariatric surgery during 2021-2023. Retro- and prospective methods were used. The results: Early and late complications were significantly reduced after the use of improved techniques. Conclusion: First of all, the use of high technologies in the implementation of LSR creates a wide opportunity to prevent its intraoperative complications. Early and late complications - metabolic acidosis, carrying out new scientific researches predicting the development of stenoses in advance and developing treatment tactics will avoid uncorrectable complications in the postoperative period.